Robust fixed-time tracking control for underactuated AUVs based on fixed-time disturbance observer. (15th December 2022) - An, Shun; Wang, Longjin; He, Yan
Abstract: This paper investigates the fixed-time trajectory tracking control problem of underactuated autonomous underwater vehicles (AUVs) subject to external disturbances. The backstepping control technique and fixed-time control method are integrated to guarantee that the trajectory of the AUV converges to the reference trajectory within a fixed-time. A continuous fixed-time disturbance observer is developed to estimate the unknown external disturbances. A nonlinear first-order filter is applied to avoid the adverse effect of "explosion of complexity" inherent in the conventional backstepping. Theoretical analyses demonstrate that under the fixed-time backstepping controller, the tracking errors of the AUV will converge towards a residual set in fixed time. Simulation results illustrate the effectiveness and superiority of the proposed control method. Highlights: A robust fixed-time backstepping controller is proposed for underactuated autonomous underwater vehicles. A continuous fixed-time disturbance observer is developed to handle the external disturbances. A nonlinear first-order filter is introduced to solve the problem of "explosion of complexity".